Analyzation of the Peripheral Blood Mononuclear Cells Atlas and Cell Communication of Rheumatoid Arthritis Patients Based on Single-Cell RNA-Seq - Xinqiang Song; Yu Zhang; Lijun Zhao; Jinke Fan; Tao Peng; Ying Ma; Nailiang Guo; Xiaotong Wang; Xudong Liu; Zhe Liu; Lei Wang (Journal of Immunology Research)
Background. Rheumatoid arthritis (RA) is a common chronic inflammatory autoimmune disease with a multifactorial etiology. Peripheral blood is the main channel of the immune system, and peripheral blood mononuclear cells (PBMCs) are the immune cells that initiate the autoimmune inflammatory process. However, there are few reports on the mechanisms of peripheral blood immunity in RA. Methods. ScRNA-seq was performed on four RA samples and integrated with single-cell transcriptome data from four healthy control samples downloaded from publicly available databases for analysis. Results. A total of 52,073 cells were used for descending clustering analysis to map RA peripheral blood immune cells at single-cell resolution. Redimensional clustering analysis of four major immune cells (T cells, monocytes, B cells, and natural killer cells) revealed that double-negative T (DNT) cells were significantly altered in abundance and function. And a number of genes (including SOCS3, cAMP-responsive element modulator (CREM), B2M, MTFP1, RSRP1, and YWHAB) were specifically downregulated in DNT cells. RA T cells, especially DNT cells, exhibit significant metabolic defects and dysfunction, mainly in the form of inhibition of oxidative phosphorylation, ATP synthesis, and major histocompatibility complex (MHC)-I-mediated antigen presentation. In addition, cellular communication networks were established, and it was evident that RA is significantly attenuated in the number and intensity of cellular communication. Monocytes and T cells play key roles in the process of the immune inflammatory response through CCL and MHC-related pathways. Conclusions. This study describes the landscape of the peripheral blood immune system and cell communication in RA, characterizes the abundance of PBMCs, gene expression profiles, and changes in signaling pathways in RA patients, and identifies several key cell subpopulations (DNT and classic monocytes) and specific genes (SOCS3, CREM, B2M, MTFP1, RSRP1, and YWHAB). Meanwhile, we propose that classic monocytes in peripheral blood may migrate to sites of inflammation in synovial tissue under the chemotaxis of the chemokines CCL3 and CCL3L1, differentiate into macrophages, secrete proinflammatory cytokines, and thus participate in the inflammatory response. These findings provide new insights for the future elucidation of the peripheral blood immune mechanisms of RA and the search for new clinical therapeutic targets.